Riparian Land Use and Hydrological Connectivity Influence Nutrient Retention in Tropical Rivers Receiving Wastewater Treatment Plant Discharge - Finkler, N. R.; Gücker, B.; Boëchat, I. G.; Ferreira, M. S.; Tanaka, M. O.; Cunha, D. G. F. (Frontiers in Environmental Science, 2021)
Riparian areas are recognized for their buffering capacity regarding phosphorus and nitrogen from agricultural and urban runoff. However, their role in attenuating nutrient loads of rivers receiving point source nutrient inputs (e.g., from wastewater treatment plants, WWTPs) is still little understood. Here, we investigated whether ammonium (NH4-N), nitrate (NO3-N), and soluble reactive phosphorus (SRP) retention were influenced by the riparian land use in three Brazilian rivers receiving WWTP effluents. We hypothesized that nutrient attenuation would be potentially influenced by the hydrological connectivity between the main channel and riparian areas with native vegetation. We estimated retention from longitudinal patterns of dilution-corrected nutrient concentrations below the WWTPs. We assessed nutrient retention during periods with high (i.e., the wet) and low connectivity (i.e., the dry season). Relationships between non-conservative (nutrients) and conservative (chloride) solutes in both seasons were used to identify potential changes in the river chemistry due to the hydrological connectivity with the riparian areas. We also evaluated the relationship between net uptake velocities (Vf-net) and the accumulated percent native vegetation cover in the 100-m buffer using linear regressions, comparing the response for each nutrient between seasons with Analysis of Covariance. Slopes of regressions between nutrients and chloride significantly differed between seasons for NO3-N and SRP but not for NH4-N. The relationships between Vf-net and accumulated native vegetation in the riparian buffer presented steeper slopes for SRP in the wet than in the dry season. No significant relationships between NO3-N Vf-net and native vegetation cover were observed in either season. In contrast, increases in Vf-net with increasing vegetation cover were observed for NH4-N in the dry season. In periods with expected higher connectivity, NO3-N and SRP concentrations tended to be lower relative to chloride concentrations, with a potential effect of native vegetation in the riparian area on SRP retention. Our results suggest that seasonal connectivity between nutrient-rich river water and riparian areas is likely to induce changes in the predominant nutrient transformation processes, thereby favoring either nutrient retention or export in such rivers.